Comparison of technological operations in processing alfalufer hay in terms of their impact on forage quality and quantity - Tokarchuk, Oleksii; Mytko, Mykola; Burlaka, Serhii; Zozulyak, Igor; Stadnik, Mykola (Technology audit and production reserves, 2025)
Haymaking is a key stage in feed production, as the choice of technological methods directly affects its quality, nutritional value, and digestibility by animals. One of the most significant challenges in this process is the mechanical loss of alfalfa leaves during harvesting and processing of the mown mass. It is well known that leaves contain the majority of protein, carotene, and other biologically active substances. Research results have confirmed the significant impact of windrow processing frequency on dry matter losses and the nutritional value of the feed. It has been established that a single windrow treatment during drying reduces dry matter losses by 2.6–4.5 % compared to multiple tedding operations. This has a positive effect on the chemical composition of the hay and promotes the preservation of essential nutrients, particularly carotene. The carotene content in the natural mass with single windrow processing reached 32.4 mg/kg in the first experiment and 30.4 mg/kg in the second, which significantly exceeds the values for hay subjected to intensive mechanical processing. Optimizing the haymaking process not only reduces nutrient losses but also shortens drying times, which is especially important under unfavorable weather conditions. Reducing the time that mown mass remains in the field minimizes the risk of feed quality deterioration due to precipitation and promotes uniform drying of stems and leaves. Thus, improving the technological processes of alfalfa haymaking enables the production of high-quality feed with a high nutrient content and stable feed characteristics. Compared to traditional harvesting methods, the use of optimized technologies helps reduce dry matter losses, increase carotene and protein content, and improve the overall nutritional value of the hay. This contributes to a more efficient supply of high-quality roughage for livestock farming, which is a crucial factor in enhancing the productivity of agricultural animals and the profitability of the industry as a whole.